White lesions that can be wiped off: A case report of oral mucosal peeling - Ambar Kusuma Astuti; Febrina Rahmayanti (Wolters Kluwer Medknow Publications, 2022)
Background: Oral mucosal peeling (OMP) refers to an asymptomatic white lesion commonly encountered in daily practice but rarely discussed in the literature. OMP can be induced by various daily oral care products. Although common, some clinicians may not be familiar with OMP. In this case report, we describe a case of widespread OMP associated with toothpaste and mouthwash use. Case Report: A 40-year-old man presented with asymptomatic white lesions, with thin sloughing appearance in the whole oral mucosa. The patient was healthy, with no routine use of medications. The lesions were easily removed using a sterile gauze, with no subsequent erosion or ulceration occurring. The lesions were attributed to the use of sodium lauryl sulfate (SLS)-containing toothpaste and a mouthwash containing chlorhexidine (CHX) and essential oils. The patient was advised about the benign nature of the lesions. Discontinuation of SLS-containing toothpaste was suggested. Conclusion: OMP is commonly associated with the use of SLS-containing toothpastes and dentifrices and mouthwashes containing essential oils or CHX with the use of SLS-containing toothpastes and dentifrices and mouthwashes containing essential oils or CHX. Dentists must be able to identify OMP and provide appropriate patient education.